The determinatin of concepts «person‒ individual‒personality» in soviet period - Sokol, Mariana (ScienceRise: Pedagogical Education, 2017)
From the middle of the twentieth century, a new period of pedagogical concepts development begins. This period caused the intensification of researches in this area and, consequently, increased the number pedagogic encyclopaedias dictionary publications. During small period have been significant changes to distinguish the main pedagogical categories. Traditionally, scientists’ attention was focused on logical and meaningful clarify pedagogical concepts. While the issue of forming global thesaurus of various fields of science, formation and development of concepts as the concentrated expression of the historically achieved pedagogical knowledge and determination of concepts «person‒individual‒personality» in the Soviet period in pedagogy weren’t decided on a conceptual level. In our research, we qualify pedagogic scientific thesaurus as a scientific and cultural phenomenon that provides an understanding of scientists and practitioners in the global educational space and coherence of methodological principles of research problems. It is also a system of concepts, which is designed for people assimilation and mainstreaming the successful orientation in the sphere of scientific knowledge subject